Gündem Belirleme Teorisi Bağlamında 30 Mart 2014 Yerel Seçimlerinin Basında Sunumu: Akp Ve Chp Örneği - Güneş, Ahmet (The Turkish Online Journal of Design Art and Communication, 2014)
Turkey is a country that has experienced local election process and/or phenomenon several times which is a political experience and takes place within the context of individual choice since the beginning of multiparty period. From the beginning of multiparty period onwards, the relation between media and politics has always been a matter of discussion. The media, which is an inseparable part of parliamentary democracies, is a concept which has played an important role in countries undergoing or having completed the process of democratization, and it is accepted as the fourth power according to pluralist liberalism approach. In this period when there are attributions such as " biased media" or "subjectivity/party bulletin" while the media is being criticized, the discussions regarding the relation between politics and media have also heated up. Within the context of this study, the political agenda of Turkish media was determined through the examples of Hürriyet, Sabah, YeniŞafak and Sözcü newspapers.The newspapers mentioned in the study has been analyzed through content analysis method.As a result of the study, we tried to obtain significant views concerning the newspapers' attitude to reflect the political agenda.
Keywords: 2014 Yerel Seçimleri; 2014 Local Elections; Gündem; Agenda; Haber; News; Agenda Setting Theory; Gündem Belirleme Teorisi; İçerik Analizi; Content Analysis